Residual Mechanical Properties of Sandstone After Fire - Ema Jankovičová; Radek Zigler; Jiří Pazderka (Buildings, 2025)
The impact of fire on natural stone structures is a critical concern, particularly for historical buildings. This study examines the residual mechanical properties of sandstone after exposure to high temperatures. Cylindrical sandstone samples were heated to temperatures up to 900 °C and subsequently tested under uniaxial compression. The results indicate that mechanical degradation becomes significant beyond 460 °C, with compressive strength decreasing by up to 43% at 900 °C. Young’s modulus also declined substantially, while axial strain increased, indicating progressive structural weakening. Additionally, visible colour changes suggest mineralogical transformations. These findings provide essential insights into the fire-induced deterioration of sandstone, offering valuable guidance for the preservation and restoration of historical stone structures.